Application auto-play media studio (AMS) 8 for learning media of logarithm function - Hartinah, Sitti; Amaliyakh Sholikhakh, Rizqi; Umam, Rofiqul; Syazali, Muhamad; Andriani, Siska; ., Mujib; Malinda, Anna; Saregar, Antomi; ., Roslina; Lestari, Fitria (International Journal of Engineering and Technology, 2019)
This study aimed to develop a mathematics learning media based on Auto-play Media Studio (AMS 8) by testing the feasibility and attrac-tiveness of learning media as well as testing the effectiveness of instructional media, especially on topic of logarithmic functions. This re-search was conducted at Senior High School of Al-Huda in South Lampung, Indonesia. This research used development methods with a 4D model from Thiagarajan. The research data was obtained from a questionnaire and tests. The questionnaire validated by the consultants of media experts, was given to students, and a set of questions of the pre-test and post-test were given to the students. The results of the assessment based on learning media of Auto-play Media Studio (AMS) 8 by rating topic expertâ€™s obtained the average value of 85.77% with very good criteria, the assessment of media experts obtained an average value of 87.61% with very good criteria. The responses assessment of students to learning media obtained an average value of 81.27% with very interesting criteria, the effectiveness assessment of learning media with n-gain test using the pre-test and post-test questions on students obtained an average value of 0.71 with high criteria. Based on the analysis data obtained by researchers, it can be concluded that the mathematics learning media based on Auto-play Media Studio (AMS) 8of logarithmic functions topic in high school is interesting and effective to be used as a learning media.Â